Fundamental Indexation in Brazil: a competitive strategy? - Roquete, Raphael Moses; Leal, Ricardo Pereira Câmara; Campani, Carlos Heitor (Review of Business Management, 2018)
Purpose – This article analyzes fundamental indexation in Brazil relative to the IBrX 100 and selected stock funds in the period between June 2003 and May 2015. This strategy relies on weights based on fundamental indicators and not on market prices. Design/methodology/approach – Fundamental indices built with the IBrX 100 stocks were weighted according to fundamental indicators. The fundamental weighting method sets the weight of each stock as proportional to a previously determined fundament value. This article also considers an ordinal weighting. Findings – The results indicate that fundamental indices do not display positive and statistically significant returns and alphas after adjusting a five risk factor model and transaction costs. The ordinal weighting suggests that fundamental indicator outliers do not drive results. The evidence also suggests that fundamental indices might perform better in bear markets. Originality/value – In general, fundamental indices behave like value stocks and do not present abnormal returns. This is consistent with the absence of fundamental index products in the Brazilian market.